Produtividade da forragem de milho e Capim-marandu integrados em sistema agrossilvipastoril com eucalipto - Domingues, Miguel Sales [UNESP] (2015)
The objective was to evaluate the development, light interception and chlorophyll content index of maize intercropped with marandu grass, the productivity of maize forage intercropped with marandu grass and development, light interception, chlorophyll content index and productivity of marandu grass intercropped or not with maize in an agrosilvopastoral system. The experiment was conducted at APTA - Andradina, SP and treatments were no eucalyptus (full sun: control) systems with eucalyptus (one and three rows) and within these five distances from trees (2, 4, 6, 8 and 10 m). Between strips eucalyptus was used integration with marandu grass with or without maize. Were evaluated in maize: plant height, ear height, chlorophyll content index, light interception, dry matter, fresh and dry matter forage. In grass tillering, height, chlorophyll content index, light interception and productivity of dry matter were evaluated. The experimental design was a randomized block in factorial arrangement with additional treatment (control) and four repetitions. The productivity of maize forage, dry matter, plant height, ear height were not influenced by the arrangements of trees. At a distance of 2 m from the trees had lower productivity, dry matter, plant height and ear height. Was difference between the values of light interception in maize distances between the first two evaluations. The heights during the development of maize were not affected by distance, or by arrangements of trees and there was no difference between the control and the agrosilvopastoral systems. Chlorophyll content index maize was not affected by distances from trees, or by arrangements and no difference between the control and the agrosilvopastoral systems. The height of the grass at distances from trees was lower in the first two evaluations. The light interception of the grass was shorter distance of 2 m from the trees in the last evaluation